Senses produced in the public school: individual guilt and possibilities of transformation (Research, Society and Development, 2017)
The purpose of this article is to reflect about guilt individual for his own failure in the school environment, understanding guilt as a product of Western society. From the analysis of the discourses of professionals and students of a public school in the State of Minas Gerais, we sought to understand the senses produced by these subjects, the possibilities of rupture with hegemonic senses, as well as the production of other senses. The methodology consisted of a qualitative and interdisciplinary study, including discussions in the areas of School Psychology and Critical Educational Psychology, Critical Social Psychology, Ethnographic Research, French Speech Analysis (AD) and Michel Foucault's theories on discourse, the subject and the knowledge-power relationship. The study revealed that school logic has generated suffering and alienation of the subjects, without there being a broader reflection on the social determinants. There are, however, possible drift points, which may point to ruptures with the hegemonic discourse.